2020
DOI: 10.14740/jocmr4323
|View full text |Cite
|
Sign up to set email alerts
|

Low-Flow Nasal Cannula Hydrogen Therapy

Abstract: Background: Molecular hydrogen (H 2) is a biologically active gas that is widely used in the healthcare sector. In recent years, on-site H 2 gas generators, which produce high-purity H 2 by water electrolysis, have begun to be introduced in hospitals, clinics, beauty salons, and fitness clubs because of their ease of use. In general, these generators produce H 2 at a low-flow rate, so physicians are concerned that an effective blood concentration of H 2 may not be ensured when the gas is delivered through a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In the H 2 -exposed group, 100% hydrogen was administered via nasal cannula at a rate of 250 mL/min with spontaneous breathing, as previously reported. 35 We confirmed that the H 2 concentration in the carotid blood during H 2 inhalation was maintained at approximately 5%. After 3 hours of LPS administration, the main trunk of the PAs was exposed through a midthoracic incision, and blood was collected from the distal part after clamping the proximal part of the PAs ( Supplemental Figure 1B ).…”
Section: Resultssupporting
confidence: 74%
“…In the H 2 -exposed group, 100% hydrogen was administered via nasal cannula at a rate of 250 mL/min with spontaneous breathing, as previously reported. 35 We confirmed that the H 2 concentration in the carotid blood during H 2 inhalation was maintained at approximately 5%. After 3 hours of LPS administration, the main trunk of the PAs was exposed through a midthoracic incision, and blood was collected from the distal part after clamping the proximal part of the PAs ( Supplemental Figure 1B ).…”
Section: Resultssupporting
confidence: 74%
“…However, our earlier study found a very high concentration of H 2 in the carotid artery after a single inhalation of the gas, confirming that inhalation is the best way to supply H 2 to the entire body through the arterial blood [ 14 ]. Another study of ours used a different experimental system in which 100% H 2 was continuously inhaled through a nasal cannula; here, the H 2 concentration in the arterial blood matched the predicted value of the fraction of inspired H 2 , i.e., the concentration of H 2 in the gas mixture [ 15 ]. This experiment proved that the H 2 concentration in arterial blood is proportional to the partial pressure of H 2 in the inhaled gas mixture.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs are specialized for gas exchange in that the thin type I alveolar epithelial cells (squamous epithelial cells), which have a thickness of 0.1–0.2 μm, are so close to the capillary wall (endothelial cells) that the two cannot be distinguished under a light microscope. In our above-mentioned experiment with inhaled H 2 , the H 2 saturation of the arterial blood instantly increased to a level comparable to the H 2 concentration in the alveoli [ 14 , 15 ]. However, the intestinal lumen is covered by a single layer of columnar epithelium, so the diffusion distance from the lumen to the capillaries is much greater than that from the pulmonary alveoli to the capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies investigating the combination of H 2 administration with other rehabilitation programs would be important future work. H 2 administration seems to be a healthy, safe [ 20 , 29 , 65 ], well-tolerated therapeutic approach with no clinically significant health issues reported in animal model [ 37 , 43 ]. Therefore, we assume that H 2 could be potentially applied at health rehabilitation facilities (spa), post-COVID-19 care units, or during telerehabilitation in post-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the operation manual, the H 2 generator provides H 2 at 99.99% purity, produced via purified water electrolysis using a membrane electrode assembly/proton exchange membrane. Inhalation of 100% H 2 produced by a H 2 generator through a nasal cannula, even at low flow rates (250 mL/min), was demonstrated to be an effective method of H 2 administration [ 43 ]. Participants could not distinguish between the inhalation of H 2 and placebo because H 2 is colorless, odorless, and tasteless [ 29 ].…”
Section: Methodsmentioning
confidence: 99%